The Contribution of the Greek Patristic Idea to the Teaching of “Lumen Gentium” on the Nature of the Church - Jeliński, Przemysław (Studia Theologica Varsaviensia, 2020)
e nature of the Church was expressed in Dogmatic Constitution on the Church “Lumen gentium” by numerous pictures and new expressions. ey refer to the Bible and patristics. It is necessary to place special attention on two expressions. ese are: the mystery of the Church and the new people of God. e Second Vatican Council used these expressions to name two of titles of chapters of Lumen gentium. In this article, the speeches of the Greek Fathers of the Church are detailed analysed. e Council document refers to them in glosses only. ` numbers – 4 in each chapter – contain references to Greek patristics. Totally, in +7 glosses to chapter I and II the Constitution refers to +5 Greek Fathers of the Church and to the anonymous patristic text of Didache. In the final part of this work the development of the patristic period was summarized in a chronological aspect. It began with Didache, then Irenaeus and John Chrysostom, and finally John of Damascus. In comparison to the whole Constitution with reference to the nature of the Church (as the mystery and new people of God) there is very little patristic inspiration. In this article, speeches of the Fathers of the Church were not only analysed, but also compared to council texts. anks to this, we see it as a short anthology of patristic ideas.